Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian Kerupuk PF di CV. Putera Fajar Medan - Winata, Clarrissa (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this study is to find out and analyze the Effect of Product Quality, Price and Service Quality on the Decision to Purchase Pf Crackers in CV. Putera Fajar Medan. The type of research used in this study is associative research. The sampling technique uses a saturated sampling method, with a sample count of 85 stores. The data analysis method used is multiple linear regression analysis. Based on the test results in the study, it shows that initially the variables of product quality, price and service quality affect the decision to buy PF crackers in CV. Putera Fajar Medan. Simultaneously, the variables of product quality, price and service quality affect the purchase decision of PF crackers in CV. Putera Fajar Medan. The value of the coefficient of determination (Adjust R Square) is 0.137 or 13.7 which means the decision to buy PF crackers on the CV. Putera Fajar Medan was influenced by product quality, price and service quality by 13.7% and the remaining 86.3% was influenced by other factors that were not studied in this study.